The Determinants of Investment in Very High Capacity Networks: A System Dynamics Approach - Richard Cadman; Stephan Curram; David Exelby (International Telecommunications Society (ITS), 2021)
European regulators of electronic communications markets are under an obligation to pursue widespread access to, and take up of, very high capacity networks, defined as being gigabit capable. Whilst there is an existing body of literature about the relationship between individual regulations and their effect on investment, less research has been conducted that places investment decisions within the market-wide broadband system. This paper seeks to address that gap by developing a generic System Dynamics model and understanding the path specific countries have taken through that model. The paper highlights a number of drivers of investment, organised around the three elements of the net present value equation: capital, net cash flow and cost of capital. It then develops a high level model before identifying the path to investment found in Ireland and Spain. The paper concludes that determinants of investment in VHCNs are path dependent and thus there is no universal strategy that will work for all countries. Competition is always an important determinant but how firms respond to competition is a function of local circumstances and legacies.
Keywords: 330